Abundance and spatial distribution of blue swimming crab (Portunus pelagicus) larvae during east monsoon in the East Lampung waters, Indonesia - DURANTA D. KEMBAREN; ZAIRION ZAIRION; MOHAMMAD M. KAMAL; YUSLI WARDIATNO (Biodiversitas Journal of Biological Diversity, 2018)
Kembaren DD, Zairion, Kamal MM, Wardiatno Y. 2018. Abundance and spatial distribution of blue swimming crab (Portunus pelagicus) larvae during east monsoon in the East Lampung waters, Indonesia. Biodiversitas 19: 1326-1333. The blue swimming crab/BSC, Portunus pelagicus, is an economically important species in fishery industry and continuously being exploited, particularly in the East Lampung waters. BSC research in Indonesia during the last decade was only restricted to the adult phase, while research on their larval dynamics in nature has not been done yet. This study aimed to assess the abundance and the distribution of BSC larvae, and to describe their correlation to its environmental conditions. This study was conducted in June 2017 (during east monsoon) in the East Lampung waters. Sampling was done in surface water during the daylight hours on nine sites with three replicates on each site. Plankton abundance and oceanographic profile were also recorded from the same sampling site. The result from this study showed that the water quality from the environment was suitable for the development of BSC larvae. The abundance of the early-stage larvae (Z1-Z3) was relatively higher than the late-stage larvae (Z4 and M). The larval stages of BSC were dispersed and completed their development in the mid-shore and offshore waters. There was a tendency that the early-stage was more abundant in the northern part, while the late-stage was more abundant in the southern part of the study area. The highest larval abundance was found in the mid-shore, particularly in site number five, which was influenced by the water mass density and current direction during the east monsoon. Moreover, oxygen concentration and salinity of the water environment influenced the early-stage larvae abundance more than the late-stages abundance.